2015
DOI: 10.1371/journal.pone.0119612
|View full text |Cite
|
Sign up to set email alerts
|

Can Acupuncture Treatment Be Double-Blinded? An Evaluation of Double-Blind Acupuncture Treatment of Postoperative Pain

Abstract: Blinding protects against bias but the success of blinding is seldom assessed and reported in clinical trials including studies of acupuncture where blinding represents a major challenge. Recently, needles with the potential for double-blinding were developed, so we tested if acupuncture can be double-blinded in a randomized study of sixty-seven patients with acute pain ≥ 3 (0-10 scale following third molar removal) who received active acupuncture with a penetrating needle or placebo acupuncture with a non-pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 33 publications
1
42
1
2
Order By: Relevance
“…Some placebo acupuncture devices that intended to mask both acupuncturist and patient were not effective to do it as acupuncturists found that it was a fake device, while the volunteers believed it was real acupuncture [43, 44]. Other studies have shown that placebo acupuncture technique is not effective to mask even the patient [1, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Some placebo acupuncture devices that intended to mask both acupuncturist and patient were not effective to do it as acupuncturists found that it was a fake device, while the volunteers believed it was real acupuncture [43, 44]. Other studies have shown that placebo acupuncture technique is not effective to mask even the patient [1, 45].…”
Section: Discussionmentioning
confidence: 99%
“…3 The patient BIs for study Ib 3 reported by Moroz et al were not appropriate. Therefore, we report practitioner-sourced BIs, which have not been presented before, along with patient BIs from five validation studies [3][4][5][6][7] (table 1). The BI (ranging from −1 to 1) is a statistical tool that can be used to objectively assess the effectiveness of blinding and has been recently introduced into acupuncture studies.…”
mentioning
confidence: 99%
“…2 Table 1 shows the BIs derived from our studies [3][4][5][6][7] employing pairs of penetrating real and skin-touch placebo needles 3 4 6 7 or penetrating real needles only. 5 The overall practitioner BIs for both penetrating real and skin-touch placebo needles indicate 'random guesses', which means that the effectiveness of practitioner blinding seems promising.…”
mentioning
confidence: 99%
See 2 more Smart Citations